Ecotourism in Kerala, India: Lessons from the Eco- Development Project in Periyar Tiger Reserve - Dr. Santosh. P. Thampi (ECOCLUB.com E-Paper Series, Nr. 13, June 2005, 2005)
The purpose of this article is to describe and evaluate the ecotourism project at the Periyar Tiger Reserve (Thekkady), in Kerala, India. The Ministry of Environment has undertaken to promote local community participation in forest management, through the "India - Eco - Development" programme in seven states. In Kerala, the `ThekkadyTiger Trail' project was launched a couple of years ago in the Periyar Wildlife Sanctuary. In the Periyar Tiger Trail project, the members involved are the former inhabitants of the forest, who use to make a living by illegal trading of forest goods. Their activity was thus detrimental to the conservation of the forest. However, their intimate knowledge about the plants and animals, and their survival instincts could be best used for participatory ecotourism activities. Besides the Tiger Trail, other ecotourism products of the Periyar Tiger Reserve are: Bamboo Rafting, Day Trekking Programme, Tribal Heritage, Bamboo Grove, Jungle Inn and Wild adventures. A brief account of Ecotourism initiatives in the Periyar Tiger Reserve and a review of the project, based on the principles of Ecotourism are included in this article